2021
DOI: 10.1371/journal.pmed.1003492
|View full text |Cite
|
Sign up to set email alerts
|

HIV incidence after pre-exposure prophylaxis initiation among women and men at elevated HIV risk: A population-based study in rural Kenya and Uganda

Abstract: Background Oral pre-exposure prophylaxis (PrEP) is highly effective for HIV prevention, but data are limited on HIV incidence among PrEP users in generalized epidemic settings, particularly outside of selected risk groups. We performed a population-based PrEP study in rural Kenya and Uganda and sought to evaluate both changes in HIV incidence and clinical and virologic outcomes following seroconversion on PrEP. Methods and findings During population-level HIV testing of individuals ≥15 years in 16 communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 53 publications
4
43
0
Order By: Relevance
“…The observed outcome of D-PrEP use in our study was similar to that reported in randomized clinical trials 2,4 and was slightly higher than that in a demonstration project in Africa. 20 Consistent with previous open-label prospective cohorts, [8][9][10] the observed outcomes of D-PrEP and ED-PrEP use were similar. Incident HIV seroconversion among PrEP users could be explained by suboptimal adherence.…”
Section: Jama Network Open | Infectious Diseasessupporting
confidence: 87%
“…The observed outcome of D-PrEP use in our study was similar to that reported in randomized clinical trials 2,4 and was slightly higher than that in a demonstration project in Africa. 20 Consistent with previous open-label prospective cohorts, [8][9][10] the observed outcomes of D-PrEP and ED-PrEP use were similar. Incident HIV seroconversion among PrEP users could be explained by suboptimal adherence.…”
Section: Jama Network Open | Infectious Diseasessupporting
confidence: 87%
“…Further work in this cohort found higher adherence to PrEP was correlated with known risk factors for HIV, suggesting that women at higher risk might choose to accept and adhere to PrEP. 19 The SEARCH study 20 reported a decrease in HIV incidence of 74% in women who initiated PrEP. Conversely, in the recently completed vaccine trial HVTN 702, 21 PrEP was not provided on-site and few initiated PrEP; HIV incidence was 4·2 per 100 person-years, comparable to ECHO before the introduction of PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…With new data available that demonstrate population-level reductions in HIV incidence in the context of community-wide HIV testing and universal access to oral PrEP [ 24 •], a critical look at risk assessment is needed to inform delivery of oral PrEP and the DVR. The field has already started to evolve, with WHO and HIV prevention experts encouraging a reframing away from risk assessment toward an assessment of interest in and readiness for oral PrEP.…”
Section: Broad Eligibility Criteriamentioning
confidence: 99%
“…In some countries (e.g., South Africa and Namibia), oral PrEP could be delivered only by nurses who had undergone nurse-initiated management of antiretroviral therapy (NIMART) training. However, these approaches did not effectively reach general population groups at substantial risk of HIV, including AGYW, who are unlikely to seek out HIV-specific service delivery channels, have concerns about stigma, and prefer low-barrier models for preventive care (e.g., limited travel, short wait times) [ 19 •, 24 •, 41 ].…”
Section: Diversified Service Delivery Channels and Approachesmentioning
confidence: 99%